Perancangan Sistem Informasi Berbasis Web untuk Objek Pariwisata di Kabupaten Pinrang - Zulvita; Sanatang Sanatang; Abdul Wahid (Progressive Information, Security, Computer, and Embedded System, 2024)
This research aims to produce a web-based Information System website for tourism objects in Pinrang Regency and determine the results of system testing using ISO 25010 which consists of 8 aspects of testing. The type of research used in this study is Research and Development (R&D), with the System Development Life Cycle (SDLC) development model. Data collection techniques using observation, interviews, and questionnaires. The results of this study, namely: (1) Functional suitability on the system that has been made is 100% "very feasible" category. (2) Usability is 96.8% of the "very feasible" category. (3) Compatibility shows that the system made is compatible with the browser so that it is declared good without any problems. (4) Performance efficiency obtained grade B with a performance of 89%. (5) Reliability obtained results with a feasibility percentage of 100%. (6) Security obtained results with threat level 2 or medium with a total of 2 medium and low warnings. (7) Maintainability obtained results from instrumentation, consistency, and simplicity can be categorized as good and meet the standards. (8) Portability shows the system can be accessed in various different browsers. Based on the test results, the web-based information system for tourism objects in Pinrang Regency can be said to be feasible and acceptable for use. Keywords: Information System, Tourism, Pinrang Regency, ISO 25010